1987
DOI: 10.1677/joe.0.1150273
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gonadotrophin-releasing hormone agonist-induced suppression of LH and FSH on follicle growth and corpus luteum function in the ewe

Abstract: Continuous infusion of a gonadotrophin-releasing hormone (GnRH) agonist (buserelin) by osmotic minipump from day 1 of the luteal phase in five Welsh ewes resulted in a sustained suppression of plasma concentrations of FSH which increased three- to eightfold within 2 days after the end of infusion 29 days later. Plasma concentrations of LH increased three- to eightfold over the first 5 days of infusion and then became basal and non-pulsatile until 1 day after the end of infusion. Duration of the luteal phase an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
86
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(96 citation statements)
references
References 27 publications
8
86
2
Order By: Relevance
“…In the synthesis of estrogen, a unique cascade (the so-called two-cell two-gonadotropin mechanism) has been demonstrated in the ovary [5]. By contrast, in cows treated repeatedly with GnRH-A, the activity of pituitary LH to stimulate thecal androgen synthesis might be almost ceased as previously reported in the ewe [14]. Therefore, injected FSH could not stimulate E 2 production because of the lack of substrate for aromatization in granulosa cells, although it exhibited FSH-like activity in granulosa cells to stimulate follicular growth and irINH secretion.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…In the synthesis of estrogen, a unique cascade (the so-called two-cell two-gonadotropin mechanism) has been demonstrated in the ovary [5]. By contrast, in cows treated repeatedly with GnRH-A, the activity of pituitary LH to stimulate thecal androgen synthesis might be almost ceased as previously reported in the ewe [14]. Therefore, injected FSH could not stimulate E 2 production because of the lack of substrate for aromatization in granulosa cells, although it exhibited FSH-like activity in granulosa cells to stimulate follicular growth and irINH secretion.…”
mentioning
confidence: 70%
“…However, a chronic treatment with GnRH or its agonists (GnRH-A) can lead to suppression of the reproductive function that includes pituitary gonadotropin secretion, ovarian follicular growth, steroidogenesis and ovulation [1,2,4,13,17,18]. Desensitization of pituitary gonadotropin secretion that induces suppression of follicle-stimulating hormone (FSH) secretion and inhibition of pulsatile release of luteinizing hormone (LH) has been reported as being a result of chronic administration with GnRH-A [14].…”
mentioning
confidence: 99%
“…Specifically, although serum progesterone concentrations rise during estrus irrespective of implant sites, there are premature declines in steroid levels starting 1 to 4 weeks after hormone implant placement. In females exhibiting such declines, circulating deslorelin remains elevated (>100 pg/ mL) 20 days after implant administration, whereas that of individuals administered via vulva mucosa decreased to undetectable levels after 12 days [30]. Thus, prolonged release of the deslorelin into circulation may cause the downregulation of pituitary gonadotropins and premature luteal failure in female domestic dogs administered deslorelin subcutaneously [27,30].…”
Section: Discussionmentioning
confidence: 99%
“…In females exhibiting such declines, circulating deslorelin remains elevated (>100 pg/ mL) 20 days after implant administration, whereas that of individuals administered via vulva mucosa decreased to undetectable levels after 12 days [30]. Thus, prolonged release of the deslorelin into circulation may cause the downregulation of pituitary gonadotropins and premature luteal failure in female domestic dogs administered deslorelin subcutaneously [27,30]. Furthermore, it has been shown that GnRH and its agonists bind to specific receptors on the luteal cells that, in turn, suppress the production of progesterone in the rat [31].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the abolition of pulsatile LH release by chronic treatment of ewes with a GnRH agonist (17) or by treating ewes with a GnRH antagonist (18) had no effect on luteal function as assessed by changes in plasma concentrations of progesterone. These authors suggested that normal progesterone secretion by the sheep CL of the oestrous cycle can be maintained in the presence of basal concentrations of LH.…”
Section: Discussionmentioning
confidence: 99%